Measuring the capacity limit in children's school bags using ESP32 microcontroller and GPS tracker - Putri Oktari; Jaka Persada Sembiring (Publikasi Indonesia, 2024)
Backpacks are the main choice for students as a means of carrying school supplies and materials, but often they do not pay attention to the weight of the load they carry every day, potentially causing injuries and pain in the back. This study aims to design and implement a capacity limit measuring device on children's school bags using the ESP32 microcontroller as the control center. The tool is equipped with a 10kg load cell sensor to accurately measure the weight of the bag, as well as a keypad as a user interface to easily enter the child's weight. Safety is also considered with the addition of a buzzer as an alarm if the weight of the bag's capacity exceeds the set limit. GPS trackers are also integrated to monitor the geographical location of bags, allowing parents to monitor the movement of children and the location of bags directly through Telegram bots. With ESP32 as the brain, this tool provides a comprehensive solution to maintain the health and safety of children in carrying their school load. This tool also utilizes Telegram technology to provide direct notifications about the weight and location of children's bags to parents or other users. Telegram bots connected to this tool automatically transmit this information, providing additional convenience and security for users.